Evaluation of Pregnancy-related Health Behaviors’ Change during Pregnancy for Pregnant Women Attending Abo Ghareeb Primary Health Care Sector - Khleel, Huda; mohammed, Widad (Iraqi National Journal of Nursing Specialties, 2021)
Objective(s): The study aims at evaluating pregnancy-related health behaviors for pregnant women, and to identify the association between pregnancy-related health behaviors and their demographic characteristics of pregnant woman’s age, education, employment, residential area and monthly income. Methodology: A descriptive study is carried out for the period from December 14th, 2020 to June 20th, 2021. This study was conducted through a non-probability (convenience) sample of 150 pregnant women attending, Abo Ghareeb primary health care sector in Abo Ghareeb spend. The sample has been collected by using the instrument to gather data and accomplish the study’s objectives. A questionnaire is composed of (29) items and it is divided into two parts. The first part is socio-demographic data of pregnant women which consists of (five) items including age, level of education, occupation, residential area, and monthly income and the second part is items of health behaviors during pregnancy which consists of (29) questions and question number twenty-nine consist of (17) items of changed behaviors. The content validity of the instrument has been determined by panel of experts and the internal consistency reliability is determined by the computation of Cronbach alpha correlation coefficient. The data are collected throughout the use of the questionnaire and the interview technique and analyzed by applying descriptive and inferential statistical data analysis approaches. Results: Results show that (30%) of the study subjects are (20-24) years old, (88%) housewives, (28.7%) are primary school graduated, 60.7% are rural residents, and (50%) of their monthly income is (300, 000-600,000) ID. The Study results show that there is a high-significant association between the study sample’s healthy behaviors and their education, monthly income, and residential area at a p-value less than (0.01). While other demographic characteristics of age and occupation has non-significant association with a p-value of higher than (0.05). Recommendations: The study recommends that the Iraqi Ministry of Health should print and distribute booklets containing all the health behaviors of pregnant women